Differentiation between small hepatocellular carcinoma (<3 cm) and benign hepatocellular lesions in patients with Budd-Chiari syndrome: the role of multiparametric MR imaging - Zandieh, Ghazal; Shahbazian, Haneyeh; Tang, Hao; Wu, Qingxia; Shaghaghi, Mohammadreza; Hazhirkarzar, Bita; Baghdadi, Azarakhsh; Afyouni, Shadi; Verde, Franco; Pawlik, Timothy; Kamel, Ihab (Frontiers in Oncology, 2023)
Objective: To investigate the value of multiparametric MR imaging to differentiate between small hepatocellular carcinoma (s-HCC) versus benign liver lesions in patients with Budd-Chiari syndrome.Methods: 12 patients with benign hepatocellular lesions and 32 patients with small (<3 cm) HCCs were assessed. MRI images were reviewed by two radiologists blinded to the patient background information; lesion T1 and T2 signal intensities and ADC values were compared with the background liver.Enhancement of lesion relative to hepatic parenchyma [(T1 Enh -T1 liver )/T1 liver ] in the arterial, venous, and delayed phases was also compared between the two groups. A multivariable logistic model was developed using these categorical measures; the predictive value of the model was tested using the Area Under the Receiver operating characteristic (AU-ROC) curve for logistic models. P-values <0.05 were considered statistically significant.Results: There were consistent differences in T1 lesion /T1 liver , and T2l esion /T2 liver , and ADC lesion /ADC liver between benign hepatocellular lesions versus the sHCC group (p<0.001, p<0.001, p = 0.045, respectively). Lesion-to-background liver enhancement in the portal venous and delayed phases was different between the benign lesions versus sHCC (p=0.001). ROC analysis for the logistic model that included the T1 ratio, T2 ratio, and portal venous enhancement ratio demonstrated excellent discriminatory power with the area under the curve of 0.94.Multiparametric MR imaging is a useful method to help differentiate benign liver lesions from sHCC in patients with Budd-Chiari syndrome.